The Role Of Boarding Schools In Forming The Character Of Students (Dormitory O Pondok Ngalah Pasuruan Islamic Boarding School) - Muawalin, Mufidatul; Kirom, Askhabul; Saifulah , Saifulah (Jurnal Pendidikan Indonesia, 2023)
The background of this research is because of the phenomena that occur in Indonesia which are very concerning, so that the decline in morale of the younger generation is decreasing. Therefore, to deal with problems related to the decline in morals and character of the younger generation, special education is needed which aims to create intelligent and good-natured young people, one of which is through Islamic boarding school education. As the goal is to educate students to become a Muslim who fears Allah SWT. And make religion as a guide in life. So Islamic boarding schools are suitable institutions in shaping the character of children in order to prepare the nation's young generation who are ready to build a better Indonesia. The purpose of this research is to find out the role of Islamic boarding schools in shaping the character of students and what characters are formed by the Ngalah Pasuruan Islamic Boarding School for students at Dormitory O at the Ngalah Pasuruan Islamic Boarding School. This research uses a descriptive qualitative approach. Data collection was carried out by means of interviews, documentation and observation. And data analysis is done through the process of data condensation, data reduction, data presentation and drawing conclusions. Then check the validity of the data by triangulating sources, techniques, and time. Based on the results of the research, it was found that at the O Dormitory of the Ngalah Pasuruan Islamic Boarding School, character building in students was obtained through learning at the Madrasah Diniyah, especially in fiqh and morals subjects and through activities in the Dormitory or Islamic Boarding School such as reciting the yellow book, interpretation, wetonan and legian friday. In addition, there are also daily activities that must be carried out by students to practice discipline and responsibility, namely daily and weekly picket schedules, this can train students in terms of togetherness and mutual cooperation between students. As for the characters formed in the students of O Dormitory Ngalah Islamic Boarding School are the characters of responsibility, courage, obligation, independence, discipline, wisdom, simplicity, and mutual cooperation in completing a job.